Parent engagement in co-design of clinical trials: the PARENT trial - Vanderloo, Leigh M. (Trials, 2021)
Evidence generated from partnering with parents to design and conduct research together may be used to refine, adjust, and modify future research approaches. This study aimed to describe the initial approaches to parent engagement in the design of the PARENT trial as well as understand parent perspectives on the acceptability and relevance of the PARENT trial and potential barriers and facilitators to participation. Parents participating in the TARGet Kids! cohort were invited to participate in a focus group, called the PARENT panel, to co-design the PARENT trial. This focus group was conducted to capture diverse individual and collective parents’ experiences. Overall methodological approaches for the PARENT panel were informed by the CIHR Strategy for Patient Oriented Research (SPOR) guiding principles (mutual respect, co-building, inclusiveness, and support) for patient engagement in research, and facilitated through the Knowledge Translation Program in the Li Ka Shing Knowledge Institute at Unity Health Toronto. Using a Nominal Group Technique, the PARENT panel provided feedback on the feasibility, relevance, and acceptability of the proposed intervention. Findings from this work will be used to further refine, adjust, and modify the next iteration of the PARENT trial, which will also serve as an opportunity to discuss the efforts made by researchers to incorporate parent suggestions and what additional steps are required for improved patient engagement.